2023
DOI: 10.2147/ppa.s386662
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Therapy for Geographic Atrophy: A Patient’s Experience

Abstract: Purpose Geographic atrophy (GA) is the advanced form of the non-neovascular (dry) type of age-related macular degeneration. Presently, GA cannot be treated. However, new therapies administered by intravitreal injection are in late-stage development. These can slow down, but do not stop or reverse, GA progression. The acceptability of these emerging therapies to people with GA is currently unknown. The present case study explores the perspectives of a person living with GA who took part in the term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…We propose that a new construct, ‘perceived safety and risk’, generates informative data related to patients' retrospective acceptability of surgical interventions. As reported above, the three papers identified that use or propose using the TFA in surgical interventions also considered the issue of risk as a potential influence on the acceptability of surgical interventions (Crombag et al, 2021; Enoch et al, 2021, 2023). These, together with the current study, suggest that perceived risk is a construct which may impact acceptability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We propose that a new construct, ‘perceived safety and risk’, generates informative data related to patients' retrospective acceptability of surgical interventions. As reported above, the three papers identified that use or propose using the TFA in surgical interventions also considered the issue of risk as a potential influence on the acceptability of surgical interventions (Crombag et al, 2021; Enoch et al, 2021, 2023). These, together with the current study, suggest that perceived risk is a construct which may impact acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…Enoch and colleagues reported they plan to explore an additional construct, patients' perception of risk of the treatment, in semi-structured interviews and via questions with Likert-type response scales. At the time of writing, results of the mixed methods study had not been reported, however, a single interview study with a trial participant, exploring retrospective and prospective acceptability of trial involvement was reported (Enoch et al, 2023). The interview guide developed for the mixed methods study was used (and not reported) and deductive data analysis was informed by the TFA.…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…This paper focuses on the perspectives and experiences of a single individual, an example of what might be termed an instrumental case study [ 13 ], whereby a single case is explored in its full complexity in order to provide illustrative insights into a broader issue. Such an approach has previously been used in ophthalmology to illustrate the complex, unique experiences of individuals living with geographic atrophy [ 14 , 15 ] and diabetic macular ischemia [ 16 ]. Analysis of Chanel’s experience of SCR is interwoven with insights derived from the relevant literature on SCD and its ocular manifestations.…”
Section: Introductionmentioning
confidence: 99%